2010
DOI: 10.1563/aaid-joi-d-09-00040
|View full text |Cite
|
Sign up to set email alerts
|

Interim Endodontic Therapy for Alveolar Socket Bone Regeneration of Infected Hopeless Teeth Prior to Implant Therapy

Abstract: The immediate placement of implants in the fresh extraction sockets of infected teeth with periradicular and periapical lesions is contraindicated because of both the infection and the loss of architecture required for proper implant placement. There are 4 approaches for implant replacement of a hopeless tooth with lesions: (1) extraction and delayed implant placement; (2) extraction, debridement, guided bone regeneration (GBR), guided tissue regeneration (GTR), and delayed implant placement; (3) extraction, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Thus, 32 studies were identified without repetition. Of the 32 studies found, six were excluded for being case report articles and three others for being review articles. Additional hand‐searching of the reference lists of selected studies yielded five additional papers .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 32 studies were identified without repetition. Of the 32 studies found, six were excluded for being case report articles and three others for being review articles. Additional hand‐searching of the reference lists of selected studies yielded five additional papers .…”
Section: Resultsmentioning
confidence: 99%
“…However, there are still some contraindications that restrict the clinical promotion of immediate implantation ( Koh et al, 2010 ). At present, socket infection has been considered as one of the most commonly faced complications of immediate implantation ( Rass, 2010 ; Narad et al, 2018 ). An incomplete pre-implantation curettage (conventional surgical treatment of infected socket before implantation) of infected tissues will leave residual bacteria around the implant which significantly increases the risk of multiple complications and ultimately results in implant failure ( Narad et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Once post-trauma stabilization has been achieved, an objective assessment of the dentition can commence. Where non-vital teeth have questionable restorability but are amenable to endodontic treatment, the primary aim of preventing the development of an apical lesion and postponing extraction can be considered an astute way of preserving the alveolar form (15,16). Maintenance of teeth in this way can aide implant provision especially where extraction and immediate placement is envisaged once growth is complete.…”
mentioning
confidence: 99%